1992
DOI: 10.1136/bjo.76.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Vitelliform macular degeneration associated with mitochondrial myopathy.

Abstract: A patient with mitochondrial myopathy is described. Examination of his fundus revealed bilateral viteiliform degeneration of the maculae. This lesion is a focal abnormality of the retinal pigment epithelium and may be a manifestation of the underlying mitochondrial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…5 Our patient developed, at the late age of 48 years, a macular lesion resembling vitelliform macular dystrophy on her right eye. Mody et al 6 reported a patient with bilateral vitelliform macular degeneration associated with mitochondrial myopathy. However, to the best of our knowledge, there have been no previous reports of such macular lesion occurring in association with KSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Our patient developed, at the late age of 48 years, a macular lesion resembling vitelliform macular dystrophy on her right eye. Mody et al 6 reported a patient with bilateral vitelliform macular degeneration associated with mitochondrial myopathy. However, to the best of our knowledge, there have been no previous reports of such macular lesion occurring in association with KSS.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient developed, at the late age of 48 years, a macular lesion resembling vitelliform macular dystrophy on her right eye. Mody et al 6 . reported a patient with bilateral vitelliform macular degeneration associated with mitochondrial myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…5. Bird Abnormality of the RPE (69,70) Abnormality of Bruch's membrane (71,72) Abnormality of the choriocapillaris (73,74) Immune system activation (75,76) Abnormal scleral rigidity (77) Mitochondrial dysfunction (78,79) Light toxicity (80)(81)(82) Nutritional deficiencies (83)…”
Section: Discussionmentioning
confidence: 99%